Persepsi dan Pemahaman Mahasiswa Mengenai UU ITE - Citra Pratiwi; Susi Yunarti (Universitas Persada Indonesia YAI, 2023)
Currently, social media is an important part of people's lives because it is a means of getting information,sharing information and even establishing relationships. Various social media can be chosen by thecommunity according to the needs they want to obtain. The presence of the Law on electronic informationand transactions (hereinafter abbreviated as UU ITE) Number 11 of 2008 and was revised in 2016 makesIndonesia a part of the global community. The ITE Law was made by the government to regulate the use ofinformation technology and protect the public from misuse of information and in electronic transactions. Thepurpose of this research is to know the perception and understanding of students about UU ITE. The theoryused in this study is the theory of perception and attribution. This research method uses descriptivequalitative, using case study method. Collecting data through interviews with students, with triangulation ofsources.The results showed that not all informants read the contents of the ITE Law, although all informantsalready knew and had positive perceptions, their understanding of the ITE Law was still lacking. Lack ofunderstanding causes not all informants to use social media wisely. Overall, students know that the ITE Lawis very important because it can maintain security on social media